The WTO Non-Discrimination Principle and Its Impact on Developing Indonesia’s Investment - Triyana Yohanes; Aloysius Wisnubroto; Theresia Anita Christiani; H. Untung Setyardi; Hajed A. Alotaibi (Legality : Jurnal Ilmiah Hukum, 2025)
This research discusses the application of the WTO non-discrimination principle to improve the global economy. However, this application is not without several negative consequences affecting Indonesia. Many domestic investors, particularly small and medium enterprises (SMEs), have gone bankrupt due to their inability to compete with large foreign investors. The exclusion of many domestic investors and the failure to achieve the goal of making Indonesian domestic investment the main investment in the country’s economy, following the application of the WTO non-discrimination principle based on Law No. 25 of 2007, prompted this research to be conducted. With a normative juridical approach, data in the form of the TRIMs Agreement, Law No. 25 of 2007, and expert opinions were collected through library research, then analysed using qualitative methods. The results indicate that the application of the WTO non-discrimination principle in Indonesia has resulted in equal treatment between foreign investment and Indonesian domestic investment, rendering many domestic investors, particularly SMEs, unable to compete with large foreign investors and bankrupt. This hampers efforts to make Indonesian domestic investment the main investment in Indonesia’s economy.  As a developing country, Indonesia should leverage the exceptional provisions in the WTO Agreement to limit the application of the principle of non-discrimination necessary to protect domestic investment and its economic interests, including its economic system.  This study compares the policies of Saudi Arabia and China, which, in implementing investment liberalisation based on the WTO Agreement, impose restrictions to protect their national economic interests.